Design and Manufacture of Water Rockets for Practicum Activities in Increasing Demand for Physics Lessons - Estu Broto, Prasepvianto (UIN Alauddin Makassar, 2023)
Physics is a field of study that is least favored by all people. This is because the understanding of physics is only limited to theories and difficult formulas. This research aims to change the paradigm that physics is difficult. There are many applications of physics, one of which is the water rocket experiment. The research activity is carried out by designing the water rocket and then making it. The water rocket is then tested to determine its stability. The finished water rocket product is used for accompanying activities in science laboratory practice. The learning method used in this activity is the field experiment method. The students are involved directly in the practical process.